MULTIDISCIPLINARY APPROACH STRATEGIES IN ELECTROPNEUMATICS COURSE LEARNING IN THE METAVERSE ERA - Achmad Romadin; Andi Muhammad Irfan; Fahri Anwar Anwar; muhammad Hasim S; muhammad Taufiq Arfah (Department of Mechanical Engineering Education, 2026)
A multidisciplinary approach has become an important strategy in vocational education to prepare graduates who are adaptable to the demands of 21st-century industry. This study offers a novel contribution by developing a multidisciplinary vocational learning model that integrates Project-Based Learning (PjBL) and Contextual Teaching and Learning (CTL) within a metaverse-oriented learning environment. The model connects real industrial automation problems, collaborative project activities, contextual learning experiences, and digital simulation to enhance students’ technical competence, critical thinking, collaboration, creativity, and professional character. This article examines the implementation and effectiveness of the multidisciplinary strategy in the Electropneumatics course. The research employed a qualitative case study approach, with data collected through interviews, observations, and documentation. The findings indicate that the integration of PjBL and CTL provides meaningful learning experiences by linking theoretical concepts with real industrial applications and digital simulation environments relevant to the Metaverse era. This approach not only improves technical learning outcomes but also fosters responsibility, discipline, teamwork, adaptability, and problem-solving skills. However, its implementation faces several challenges, including human resource readiness, cross-disciplinary curriculum alignment, lecturer competence in digital learning design, and adequate access to digital infrastructure. Therefore, continuous evaluation and synergy among academia, industry, and government are needed to support sustainable implementation. Overall, this multidisciplinary learning model contributes to the development of innovative, contextual, and industry-relevant vocational education, particularly in preparing excellent workers in the field of industrial automation.